Investigation of X-ray radiation response to electrical properties of Mo/Cu(In0.7Ga0.3)Te2/p-Si/Al semiconductor diode - Güven Çankaya; Semra Arslan; Semih Ağca (Journal of New Results in Science)
Diodes are exposed to radiation in many operating environments, and it is important to investigate the radiation effect. In this study, the impact of X-ray radiation on the electrical properties of Mo/Cu(In0.7Ga0.3)Te2/p-Si/Al semiconductor diode was explored by I-V measurements performed before and after radiation doses between 200 and 1000 centiGray. The semiconductor diode was exposed to radiation by a linear accelerator having 6 MV X-ray. I-V measurements and the Cheung-Cheung method demonstrated the differences in series resistance, ideality factor, and barrier height. Moreover, the interface state density was obtained from I-V results. The radiation dose increased the ideality factor and decreased the barrier height. This result was thought to be due to the increase in the interface state density and the defects in the diode interface. The series resistance was increased by increasing the radiation dose due to a possible decrease in mobility and free carrier concentration. As a result of exposure to X-ray, defects occurred and due to these defects, the diode deviated from the ideal. It has been observed that the electrical properties of the diode were sensitive to X-ray radiation. The study demonstrated that the Mo/Cu(In0.7Ga0.3)Te2/p-Si/Al semiconductor diode can be implemented in X-ray radiation detection systems.